›Mos uetustissimus‹ - Tito Livio e la percezione della clemenza - Della Calce, Elisa (CICERO - STUDIES ROMAN THOUGHT RECEPTION OA, 2023)
Clemency plays an important role in Livy and his value system. Clemency is invoked, exercised or denied in three areas: family, justice and army. What emerges is a complex understanding of this value concept, which relates to various contexts and characters, evolves throughout the course of the Livy's work and is also influenced by the political environment contemporary to Livy.